Nilai Sosial dalam Novel Ibu, Doa yang Hilang Karya Bagas D. Bawono - Lian Pitasari; Nur Nisai Muslihah; Dian Ramadan Lazuardi (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
Target of research is to social value mendeskripsikan in novel Ibu, Doa yang Hilang of Bagas D. Bawono which consist of human life reality, human being masterpiece reality, reality domicile time dang space, human being relation reality with human being relation reality and nature with humanity. This research use method qualitative. Technique data collecting at this research with documentation technique, technique note, and code technique, selection technique, dekskripsi technique, conclusion technique and data verification technique. Pursuant to result of novel analysis Ibu, Doa yang Hilang of Bagas D. Bawono which have been done, indicating that human life reality there are 18 citation, human being masterpiece reality 8 citation, reality domicile time and space 10 citation, human being relation reality with nature 1 human being relation. Reality and citation with humanity 40 citation. Hence can be concluded that in novel Ibu, Doa yang Hilang of Bagas D. Bawono consist in social value related to human life reality, human being masterpiece reality, reality domicile time dang space, human being relation reality with nature, and human being relation reality with humanity. Keyword: Analysis, Social, and Novel.